Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1932296820974748
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring for the Detection of Hypoglycemia in Patients With Diabetes of the Exocrine Pancreas

Abstract: Background: Detailed evaluations of hypoglycemia and associated indices based on continuous glucose monitoring (CGM) are limited in patients with diabetes of the exocrine pancreas. Our study sought to evaluate the frequency and pattern of hypoglycemic events and to investigate hypoglycemia-specific indices in this population. Methods: This was a cross-sectional study comprising 83 participants with diabetes of the exocrine pancreas. CGM and self-monitoring of blood glucose (SMBG) were performed on all particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…‘brittle diabetes’) [7]. A recent pilot study based on continuous glucose monitoring supports this concern [30].…”
Section: The Spectrum Of Diabetes In Pancreatitismentioning
confidence: 99%
“…‘brittle diabetes’) [7]. A recent pilot study based on continuous glucose monitoring supports this concern [30].…”
Section: The Spectrum Of Diabetes In Pancreatitismentioning
confidence: 99%
“…Additionally, several retrospective studies in the 1970s suggested that diabetes secondary to pancreatic diseases is characterized by a more unstable (i.e., ‘brittle’) pattern of glycemic control [18,19]. A modern study using continuous glucose monitoring found that 90% of people with diabetes secondary to pancreatic disease experienced an episode of hypoglycemia (of whom 29% had symptoms) [20]. The study also reported that the period between 3 a.m. and 6 a.m. was the most common time for hypoglycemia in this setting.…”
Section: What Is the Clinical Significance Of Differentiating Diabete...mentioning
confidence: 99%
“…21 The authors of a cross-sectional study evaluated the superiority of CGM-derived hypoglycemic indices to identify nocturnal and asymptomatic hypoglycemic episodes in 83 PwD of the exocrine pancreas. 22 Another study comprising 5901 patients with T2D used CGM to find the association between AGP indicators and diabetes-related complications. The results indicated that those with both the hypo and hyper profiles, which can only be detected by CGM, had a higher risk of non-proliferative diabetic retinopathy (NPDR), macroalbuminuria, and diabetic kidney disease.…”
Section: Real-world Evidence On the Success Metrics Of Digital Technologiesmentioning
confidence: 99%